Analyzing motivational determinants of shopping addiction tendency - Kirezli, Özge (Ege Akademik Bakış, 2019)
ABSTRACT: Shopping addiction tendency is defined as being so occupied about shopping that consumers become driven by uncontrollable shopping urges and as a result of facing negative psychological, social and financial consequences. Based on a field study on university students (N=372), this paper examines hedonic shopping, escapism and negative mood reduction, as motivational determinants of shopping addiction tendency, which is a relatively less studied area of consumer behavior in Turkey. The findings indicate that, hedonic shopping, escapism and negative mood reduction all have significant effect on shopping addiction. Getting its mainstream studies from compulsive buying literature, shopping addiction literature focuses mainly on the enjoyment gathered from shopping action However this study provides new insights into potential antecedents of shopping addiction as negativity avoidance and escapism, which are negative psychological states with respect to shopping addicts quest for shopping enjoyment.

ÖZET: Alışveriş bağımlılığı; bireylerin iç ve dış faktörlerden kaynaklanan psikolojik gerilimleri ile baş etmek adına yapılan kontrolsüz ve aşırı alışveriş yapma olarak tanımlanabilir. Üniversite öğrencileri üzerinde yapılan bir saha çalışması doğrultusunda (N=372), bu çalışma alışveriş bağımlılığına motivasyonel anlamda etkisi olduğu düşünülen hedonik alışveriş, gerçeklerden kaçış ve olumsuz ruh halini düzeltme faktörlerini incelemektedir. Araştırmanın sonuçları, her üç bağımsız değişkenin de alışveriş bağımlılığını anlamlı biçimde etkilediğini ortaya koymaktadır. Satın alma ve alışveriş bağımlılığı literatüründe bu çalışmayı farklı kılan unsur, bağımsız değişken olarak keyif ve ruh halini düzeltme gibi psikolojiyi olumlu etkisi olan öğelerle negative bir durum olan bağımlılığı açıklamaya çalışma hedefidir. Zira, bağımlılık literatürü çoğunlukla negatif olay ne nedenler üzerinde durmaktadır.
Alışveriş bağımlılığının motivasyonel öğelerinin belirlenmesi
Keywords: Shopping Addiction Tendency; Hedonic Shopping; Negative Mood Reduction; Escapism; Alışveriş Bağımlılığı Eğilimi; Satın Alma Bağımlılığı Eğilimi; Hedonik Tüketim; Gerçeklerden Kaçış; Negatif Ruh halini Düzeltme